Comparison of computer simulation and graphical illustration for teaching experimental pharmacology to undergraduate students - Kaur, Gurleen; Garg, Preeti; Sharma, Vidushi; Singh, Jaspreet; Matreja, Prithpal Singh; Khanna, P. M. L. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Nowadays, medical schools all over the world are incorporating newer methods of teaching experimental pharmacology like computer simulation, besides using graphs, charts, didactic lectures. The present study compared the effectiveness and acceptance of two commonly used methods, namely, computer simulation and graphical illustration in teaching experimental pharmacology to undergraduate medical students. Methods: 90 students of 2nd Prof MBBS were divided into 2 groups and were given either computer simulation or graphical illustration via a cross-over design at two settings, which was followed by a post-test for that particular session. Feedback was taken from the students and the faculty. The data obtained was analyzed using descriptive statistics. Results: The average marks scored by the students in sessions using CAL (67.8%) was significantly high (p=0.008) as compared to teaching by graphical illustrations (60.4%). 71% of students found CAL improved their learning skills better than graphical illustrations. 85% students and 80% faculty agreed that there should be a judicious mixture of CAL and graphical illustrations for a better understanding of drugs. Conclusions: CAL is a beneficial and effective learning tool in teaching experimental pharmacology. For better understanding, graphical illustrations should be used as an adjuvant to CAL.